Konseptual, Strategi, dan Implementasi Blue Economy dalam Pengelolaan Perikanan Laut dan Air Tawar - Kaunang, Sandra Dewi Elizabet; Amanda, Talitha; Suhana; Marlianingrum, Peggy Ratna; Pahlevi, Muhamad Reza; Nusantara, Taufan Setia (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
The Blue Economy is a sustainable development concept that emphasizes the balance between economic growth and the sustainability of marine resources and freshwater fisheries. This article aims to analyze the concept, strategy, and implementation of the Blue Economy in marine and freshwater fisheries management in Indonesia. Using descriptive qualitative methods, this study explores aspects of innovation, policy, and challenges faced in implementing the Blue Economy in the fisheries sector. The results show that although the Blue Economy has great potential to improve the welfare of coastal communities and fish farmers, challenges such as lack of infrastructure, suboptimal regulations, and public awareness remain major obstacles. Therefore, a more integrated strategy is needed, such as digitalizing the fisheries sector, increasing the capacity of fishermen, and strengthening synergies between the government, academia, and the private sector. Thus, the implementation of the Blue Economy can have a positive impact on the sustainability of fisheries ecosystems and the economic welfare of coastal communities. The results indicate that the implementation of the Blue Economy has a positive impact on improving the welfare of fishermen and the sustainability of aquatic ecosystems.